1995
DOI: 10.1073/pnas.92.4.1157
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of protein tyrosine phosphorylation in rat insular cortex after conditioned taste aversion training.

Abstract: Protein tyrosine phosphorylation is a major signal transduction pathway involved in cellular metabolism, growth, and differentiation. Recent data indicate that tyrosine phosphorylation also plays a role in neuronal plasticity. We are using conditioned taste aversion, a fast and robust associative learning paradigm subserved among other brain areas by the insular cortex, to investigate molecular correlates of learning and memory in the rat cortex. In conditioned taste aversion, rats learn to associate a novel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 34 publications
3
46
1
Order By: Relevance
“…Similarly, because rats in group Devalue would respond to sweet with aversive responses, by associatively activating a perception of sweetness, the tone would provoke aversive responses in that group. Notably, although GC is not critical to basic functions of taste detection (e.g., Dunn and Everitt 1988), it has been shown to be importantly involved in many aspects of higher-level processing of taste memories (e.g., Braun et al 1982;Rosenblum et al 1995Rosenblum et al , 1997. Most relevant to the present study, Kiefer and Orr (1992) found that rats with GC lesions failed to replace appetitive taste-reactivity responses to a sweet flavor with aversive responses after flavor-illness pairings, even under circumstances under which those lesioned rats successfully learned to suppress overall consumption of that flavor.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, because rats in group Devalue would respond to sweet with aversive responses, by associatively activating a perception of sweetness, the tone would provoke aversive responses in that group. Notably, although GC is not critical to basic functions of taste detection (e.g., Dunn and Everitt 1988), it has been shown to be importantly involved in many aspects of higher-level processing of taste memories (e.g., Braun et al 1982;Rosenblum et al 1995Rosenblum et al , 1997. Most relevant to the present study, Kiefer and Orr (1992) found that rats with GC lesions failed to replace appetitive taste-reactivity responses to a sweet flavor with aversive responses after flavor-illness pairings, even under circumstances under which those lesioned rats successfully learned to suppress overall consumption of that flavor.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were later corroborated in vivo in the dentate gyrus of rats (Rosenblum et al, 1996;Rostas et al, 1996). Since then, tyrosine phosphorylated content of NR2B was shown to increase in response to several learning paradigms, including learning of fear (Kojima et al, 2005;Nakazawa et al, 2006) and of taste aversion (Rosenblum et al, 1995;Miyakawa et al, 1997). However, despite the strong correlation between the increase in tyrosine phosphorylation of NR2B and novel taste learning, it has not been determined whether it is necessary for learning a new taste.…”
Section: Introductionmentioning
confidence: 88%
“…We investigated the possible effect of Src40-49Tat on two forms of NMDAR-dependent learning and memory: contextual fear conditioning 29 and conditioned taste aversion 30,31 . In both tasks, we administered Src40-49Tat prior to training and then examined memory 3 days later.…”
Section: Src40-49tat Does Not Affect Learningmentioning
confidence: 99%